An overview of the use of photocatalysis in the environmental control of textile effluent - Masiren Emyra Ezzaty; Ong Huei Ruey; Khan Md Maksudur Rahmad (E3S Web of Conferences)
This study offers a thorough examination of the use of photocatalysts in textile effluent management for environmental goals. Textiles are produced on a big scale to fulfil human requirements and have become an essential part of daily life. Clothes and textiles are essential components of contemporary civilisation and human existence. As the market for textile products has grown, so too has the number of textile mills and the waste they produce, creating a significant global pollution problem. Numerous materials used in the textile industry provide serious risks to human health and the environment. A vast array of speciality chemicals, like as softeners, stain-releasing agents, saturating agents, fixing agents, and different organic dyes, are used in the textile industry. This technique has resulted in the discharge of colourants and other dye-laden effluents into river systems. This research focusses on three key areas: (i) the definition and operation of textile wastewater; (ii) the use of photocatalysts in textile wastewater treatment; and (iii) the impact of nanophotocatalysts and irradiation absorption rate on the treatment efficiency of textile wastewater. One effective way to lower the number of pollutants in textile effluent before releasing it into aquatic bodies is by photocatalytic treatment. This tactic aids in achieving the main objectives of preserving the integrity of water resources and lessening the negative environmental effects of waste from the textile sector.